Synthesis and characterization of Ni-A1₂O₃-Cr, Ni-A1₂O₃-SiC and Ni-SiC-Cr nano hybrid composites - Masoudi, Mehran (2013)
This research is focused on the preparation of nickel base composites having nano particles of chromium, alumina and silicon carbide in the form of mono and hybrid composites by using a co-electrodeposition technique in nano powders of SiC, Cr,and Al2O3 with a 50 nm mean dimension were introduced into the conventional nickel plating Watt‘s bath. The prepared new hybrid composites, mono nickel based composites and pure nickel layers were subjected to different tests to characterize their surface morphology, crystalline structure, mechanical properties and hot oxidation resistance. The microstructure and composition of the composite films were studied with field emission scanning electron microscopy (FE-SEM), XRD spectroscopy and EDS techniques. Micro hardness and wear tests were carried out on coated samples to investigate the mechanical properties. The test results showed effectiveness and flexibility of the co-electrodeposition technique in creating mono and more complicated nickel base composite layers. The novel Ni-Al2O3-Cr composite layer showed considerable improvement in hot oxidation resistance compared to the pure nickel layer and the Ni-Al2O3 composite;and it enhanced mechanical properties compared to Ni and Ni-Cr composite films. This newly created hybrid composite could be a good substitution for commercial Ni-Al2O3 and Ni-Cr composites. The fabricated novel Ni-Al2O3-SiC composite film showed superior mechanical properties among all the mono and hybrid composites studied in this research; and,by comparison with the Ni-Al2O3 composite, exhibited enhanced hot oxidation resistance. Its high hardness and wear resistance along with acceptable thermal stability makes the Ni-Al2O3-SiC composite film a good choice for coating many industrial parts and components as an anti-oxidation and anti-wear protective film. The newly fabricated Ni-SiC-Cr nanocomposite coating displayed the highest hot oxidation resistance among all the tested composites in this study owing to chromium‘s excellent corrosion and oxidation resistant properties. Advantageously, it formed silicon oxide that reduced the diffusion rate at elevated temperatures. The SiC hard and anti-wear particles rendered good mechanical properties to the synthesized hybrid composite. The altered surface morphology, fine crystalline structure, advanced oxidation resistance and improved mechanical properties enable Ni-SiC-Cr composite films to protect metallic parts in high severe corrosive, abrasive and thermal working conditions. A quantitative technique for measuring grain boundary volume percentage using XRD test results have been suggested and tested successfully in this thesis. This technique could be a reliable base for future fundamental studies on nano materials deformation mechanisms. The achievements of the project work laid out in detail in this thesis can be summarized in the following points: 1. Successful co-electrodeposition of the Ni- Al2O3, Ni-SiC and Ni-Cr mono composites by an electroplating technique. 2. Preparation of novel Ni-Al2O3-Cr hybrid nanocomposite coatings with excellent mechanical properties, improved anti-oxidation by 55% and attribute advanced thermal resistance. 3. Preparation of novel Ni-Al2O3-SiC hybrid nanocomposite coatings with superior mechanical properties (three times harder than pure nickel film) and improved hot oxidation resistance. 4. Preparation of novel Ni-SiC-Cr hybrid nanocomposite coatings having superior hot oxidation resistance (90% better than pure nickel film) and improved mechanical properties especially wear resistant behaviour. 5. Detailed study and discussion on the surface morphology, crystalline structure and texture of the created mono and hybrid composite layers. 6. Detailed study comparative on mechanical characterizations of a pure nickel film and mono as well as hybrid composite coatings. 7. Detailed study on the oxidation kinetics of prepared MMC coated samples having different varieties in the form of Cr, SiC and Al2O3 filler substances. 8. Formulation of a new quantitative technique for measuring the grain boundary volume percentage in polycrystalline materials.